THE EFFECTIVENESS OF PEER FEEDBACK ON STUDENTS’ SKILL IN WRITING NARRATIVE TEXT AT TENTH GRADE OF SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR - Binti Bakar, Suriani; Saiful; Setiadi, Muhammad Astrianto (English Language Teaching Methodology, 2024)
This research aimed to find out whether peer feedback is effective to improve the students’ writing skill in the narrative text in the tenth grade of SMA Muhammadiyah 1 Unismuh Makassar. This research employed a quantitative method with a pre-experimental design that used pre-test and post-test. The instrument of this research was a writing test. The sample of this research was the students from the tenth grade of SMA Muhammadiyah 1 Unismuh Makassar consisted of 20 students. The sample was taken by using a purposive sampling technic. The research findings showed that there was a significant difference on students’ skill in writing narrative text through peer feedback. The students’ mean score in writing on the pre-test was 72,25. Then in the post-test, the students’ mean score in writing was 84,6. The value of the t-test was higher than the t-table which was 12,47>1,729. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that peer feedback is effective to improve the students’ skill in writing narrative text.